Observations of the October Draconid outburst at different latitudes along 120°E. Issue 4 (14th September 2022) - Li, Yi; Li, Guozhu; Hu, Lianhuan; Zhao, Xiukuan; Sun, Wenjie; Xie, Haiyong; Yang, Sipeng; Ning, Baiqi
ABSTRACT: The observations of short-duration meteor showers at different geographic locations are important for well understanding of their outbursts. Using the four all-sky interferometric meteor radars at Mohe (53.49°N, 122.34°E), Beijing (40.3°N, 116.19°E), Wuhan (30.54°N, 114.34°E), and Ledong (18.44°N, 108.97°E) in China, four outbursts (2011, 2012, 2018, and 2019) of the October Draconid meteor shower were observed between 2011 and 2021. The October Draconid meteor velocity was concentrated around 22∼23 km s −1, with an active duration of 6∼9 h and a main peak around the solar longitude 194.73°∼195.63°. When comparing the hourly rates of the October Draconid meteor shower for different years at Mohe, a maximum (minimum) of peak flux was observed in 2012 (2011). The radiants and orbit parameters of the October Draconid meteors derived from the radars at different latitudes are consistent, except that the weighted mean echo height during the peak activity at Mohe was always lower than that at other stations.